Search Computing Trends and Developments - Ceri, Stefano; Brambilla, Marco (Springer eBooks., 2011)
Search computing, which has evolved from service computing, focuses on building the answers to complex search queries by interacting with a constellation of cooperating search services, using ranking and joining of results as the dominant factors for service composition. The field is multi-disciplinary in nature, and takes advantage of contributions from other research areas such as knowledge representation, human-computer interfaces, psychology, sociology, economics and legal sciences. This second Search Computing book is divided into eight parts focusing on the search process, interaction design, semantic description, rank join, query processing, tools and mashups, bio-seco, and sustainable exploitation reflecting the many research directions of the Search Computing project (SeCo).